Modeling and Experiment of the Current Limiting Performance of a Resistive Superconducting Fault Current Limiter in the Experimental System - Liang, Fei (2015)
In this paper, a 220-V resistive superconducting fault current limiter (SFCL) prototype is built and tested under different prospective fault currents, which vary from 0.8 to 7.4 kA. A 2D superconductor model is integrated into an experimental circuit model in COMSOL to simulate the performance of the SFCL prototype in the experimental system in fault tests. In the simulation, a new E-J relationship is proposed to enhance the convergence of calculation. Comparison between simulation results and experimental results shows that the proposed model performs well in simulating current limiting performance of SFCL in experimental system in case of fault.